Exploring Determinants for Enhancing Employee Performance - Hisarma Saragih; Yusuf Ronny Edward; Asep Suherman; Elizabeth; Anindya Putri Pradiptha (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to test, uncover, and investigate the function of decision variables in order to improve staff performance at the North Sumatra Community and Village Empowerment, Population, and Civil Registry Office. This was a quantitative study with 50 respondents using various approaches. To gather data, questionnaires were given to every sample. The SPSS Version 26.0 program was used to process the obtained data before it was subjected to statistical formula analysis, more precisely multiple linear regression analysis. The results of the study show that individual traits have a partially positive and significant impact on worker performance, the work environment has a partially positive and significant impact on worker performance, and workload has a partially positive and insignificant impact on worker performance. The interaction of personal characteristics, workload, and workplace conditions has a favorable and substantial impact on worker performance. The study's conclusions suggest that, in order to sustain present achievements, the management of the North Sumatra Community and Village Empowerment, Population and Civil Registry Office should pay more attention to workplace issues, especially those pertaining to employee characteristics and workload.